Maternal and Paternal Imprisonment and Children's Social Exclusion in Young Adulthood - Foster, Holly (2015)
The United States has entered its fourth decade of high imprisonment levels. It is now possible to assess the impact of parental imprisonment on children who have completed the transition to adulthood. We elaborate the role of parental incarceration from a life course perspective on intergenerational social exclusion in young adulthood. The National Longitudinal Study of Adolescent Health [Add Health] representatively sampled the historically unique national cohort born in the 1980s, during the onset of mass incarceration. Four waves of the Add Health survey provide a valuable moving window on incarcerated parents and the transitions of their children from adolescence, through school, to young adulthood. We focus on four young adult outcomes as indicators of social exclusion: personal income, household income, perceived socioeconomic status, and feelings of powerlessness. Our findings indicate that both maternal and paternal incarceration significantly contribute to young adult social exclusion among offspring in their late twenties to early thirties. Successful completion of college is a mediator of the exclusionary effects of maternal and paternal incarceration, reducing parental imprisonment effects 14%–50% (net of college completion of the mothers and fathers and a comprehensive set of further controls). This mediating college effect is consistent with other growing evidence of the salience of the college/non-college divide as an exclusionary barrier in American society. The implication is that prisons and schools are now strongly linked institutions in the intergenerational reproduction of American socioeconomic inequality